2013
DOI: 10.1002/chem.201300995
|View full text |Cite
|
Sign up to set email alerts
|

Primary–Tertiary Diamine/Brønsted Acid Catalyzed C–C Coupling between para‐Vinylanilines and Aldehydes

Abstract: Aromatic enamines: para‐Vinylanilines were identified as unique nucleophiles, closely resembling enamines, to undergo CC coupling with aldehydes catalyzed by a simple primary–tertiary diamine/Brønsted acid. The resulting bis(allylic) adducts, which have potential as functional materials, were obtained in high yields under rather mild conditions (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Therefore, we limited our discussions to those with explicit C–H bond activation or C–H bond cleavage as the key product-determining steps. The typical Heck-type processes as well as electron-tuning alkene functionalization reactions, such as reactions with enamine, enamide, or aromatic enamines, are also excluded. …”
Section: Sp2 C–h Bond Functionalizationmentioning
confidence: 99%
“…Therefore, we limited our discussions to those with explicit C–H bond activation or C–H bond cleavage as the key product-determining steps. The typical Heck-type processes as well as electron-tuning alkene functionalization reactions, such as reactions with enamine, enamide, or aromatic enamines, are also excluded. …”
Section: Sp2 C–h Bond Functionalizationmentioning
confidence: 99%
“…Alkenes are seldom utilized in conjugate addition reactions because of their low nucleophilicity as well as the uncontrolled side reactions accompanying such processes. We recently found that p -vinylanilines 33 , endowed with an intervening aromatic ring between the amine and vinyl group, demonstrated nucleophilic reactivity closely resembling that of typical enamines . These alkene nucleophiles were also tested in the enantioselective α-protonation reaction .…”
Section: Enantioselective Transformations Of α-Branched Vinyl Ketonesmentioning
confidence: 99%
“…Simple alkenes have rarely been utilized in asymmetric conjugate addition reactions due to the low nucleophilicity and uncontrolled side reactions . Recently, only the Luo group realized the first example of the asymmetric conjugate addition of para -vinylanilines to enones catalyzed by chiral primary amines (Scheme b) . Despite these impressive advances, development of efficient and highly enantioselective protocols for conjugate addition of unactivated alkenyl nucleophiles is still in great demand.…”
mentioning
confidence: 99%